Association between spinal stenosis and wild-type ATTR amyloidosis. (2nd October 2021) - Godara, Amandeep; Riesenburger, Ron I.; Zhang, Diana X.; Varga, Cindy; Fogaren, Teresa; Siddiqui, Nauman S.; Yu, Anthony; Wang, Andy; Mastroianni, Michael; Dowd, Richard; Nail, Tara J.; McPhail, Ellen D.; et al.
Abstract: Age-related cardiac amyloidosis results from deposits of wild-type tranthyretin amyloid (ATTRwt) in cardiac tissue. ATTR may play a role in carpal tunnel syndrome (CTS) and in spinal stenosis (SS), indicating or presaging systemic amyloidosis. We investigated consecutive patients undergoing surgery for SS for ATTR deposition in the resected ligamentum flavum (LF) and concomitant risk of cardiac amyloidosis. Each surgical specimen (LF) was stained with Congo red, and if positive, the amyloid deposits were typed by mass spectrometry. Patients with positive specimens underwent standard of care evaluation with fat pad aspirates, serum and urine protein electrophoresis with immunofixation, free light-chain assay, TTR gene sequencing and technetium 99 m-pyrophosphate-scintigraphy. In 2018–2019, 324 patients underwent surgery for SS and 43 patients (13%) had ATTR in the LF with wild-type TTR gene sequences. Two cases of ATTRwt cardiac amyloidosis were diagnosed and received treatment. In this large series, ATTRwt was identified in 13% of the patients undergoing laminectomy for SS. Patients with amyloid in the ligamentum flavum were older and had a higher prevalence of CTS, suggesting a systemic form of ATTR amyloidosis involving connective tissue. Further prospective study of patients with SS at risk for systemic amyloidosis is warranted.